2018
DOI: 10.1038/s41598-018-36121-9
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of primary B cells minimally influences their signaling responses

Abstract: Phospho flow is a powerful approach to detect cell signaling aberrations, identify biomarkers and assess pharmacodynamics, and can be performed using cryopreserved samples. The effects of cryopreservation on signaling responses and the reproducibility of phospho flow measurements are however unknown in many cell systems. Here, B lymphocytes were isolated from healthy donors and patients with the B cell malignancy chronic lymphocytic leukemia and analyzed by phospho flow using phospho-specific antibodies target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…of immune cells to freezing compared to other cell types, also observed in other settings 21 , and the lack of a dissociation step in CLL scRNA-Seq (see Methods). Cryopreservation, however, can increase the proportion of damaged cells 22 and may not successfully recover all the malignant and other non-malignant cells in the tumor.…”
Section: Nature Medicinementioning
confidence: 76%
“…of immune cells to freezing compared to other cell types, also observed in other settings 21 , and the lack of a dissociation step in CLL scRNA-Seq (see Methods). Cryopreservation, however, can increase the proportion of damaged cells 22 and may not successfully recover all the malignant and other non-malignant cells in the tumor.…”
Section: Nature Medicinementioning
confidence: 76%
“…In particular, in CLL, we successfully recovered the expected cell types from a cryopreserved sample, containing viable cells. This reflects the increased resilience of immune cells to freezing compared to other cell types, also observed in other settings(Hermansen et al, 2018), and the lack of a dissociation step in CLL scRNA-Seq ( Methods ). Cryopreservation, however, can increase the proportion of damaged cells(Guillaumet-Adkins et al, 2017) and may not successfully recover all the malignant and other non-malignant cells in the tumor.…”
Section: Resultsmentioning
confidence: 77%
“…94 The method gives highly reproducible results, and cryopreservation does not affect signalling responses in B lymphocytes. 95 By performing high-throughput phospho flow experiments in a 96-well plate format, changes in phosphorylation level of 35 proteins in response to short (20 minutes) treatment with the BTK inhibitor ibrutinib and the PI3K inhibitor idelalisib was systematically analysed in CLL cells. 89 Results showed that the targeted agents primarily affect proteins in the BCR signalosome and in the PI3K pathway.…”
Section: Cell Signalling Analysis By Phospho Flowmentioning
confidence: 99%
“…Application of phospho flow has provided valuable information about baseline and drug‐induced cell signalling in several haematological malignancies, including CLL, 39,43,88,89 acute myeloid leukaemia (AML) 90‐92 and non‐Hodgkin lymphomas, 93 as well as in normal haematologic subsets present among the malignant cells 94 . The method gives highly reproducible results, and cryopreservation does not affect signalling responses in B lymphocytes 95 . By performing high‐throughput phospho flow experiments in a 96‐well plate format, changes in phosphorylation level of 35 proteins in response to short (20 minutes) treatment with the BTK inhibitor ibrutinib and the PI3K inhibitor idelalisib was systematically analysed in CLL cells 89 .…”
Section: Bcr Inhibitors May Facilitate Implementation Of Functional Pmentioning
confidence: 99%